Clinical Aspects of Stevens-Johnson Syndrome/Toxic Epidermal Necrolysis With Severe Ocular Complications in India - Shanbhag, Swapna S.; Sangwan, Virender S.; Singh, Aastha; Donthineni, Pragnya R.; Basu, Sayan; Srinivasan, Bhaskar; Agarwal, Shweta; Iyer, Geetha (Frontiers in Medicine, 2021)
Stevens-Johnson syndrome/toxic epidermal necrolysis (SJS/TEN) is a spectrum of rare, severe immunological blistering skin reactions which are triggered by medication intake or infections. The acute phase is characterized by necrolysis of the skin and desquamation of mucosa, primarily oral and ocular, with significant mortality rates. The chronic phase is characterized by multi-organ sequelae with increased rates of morbidity and reduced quality of life for patients who have survived the acute phase. Since the primary goal in the acute phase is saving the life of the patient, ocular involvement is often missed and a significant proportion of patients present to an ophthalmologist with the chronic ocular sequelae. In India, chronic ocular sequelae and low vision are observed in two-thirds of patients who present in the chronic phase of SJS/TEN. In the chronic phase of ocular involvement, there are definite windows of opportunity which if targeted with specific interventions such as scleral lenses and mucous membrane grafts can help reduce the incidence of corneal blindness and improve the quality of life for patients with SJS/TEN. Over the last decade, several studies from India have advanced the understanding of the natural course of ocular involvement in SJS/TEN and the outcomes of timely interventions in the chronic phase of the disease. We present an overview of the epidemiology of ocular complications of SJS/TEN in India, the specific challenges faced in the management of ocular complications in the acute stage and recent advances in management of the chronic ocular complications of the disease.